2021
DOI: 10.20986/revesppod.2021.1609/2021
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento mediante descompresión del neuroma de Morton: visión actual y recomendaciones

Abstract: El neuroma de Morton, o neuroma interdigital, es una neuropatía por atrapamiento del nervio plantar digital común en la que el ligamento transverso metatarso profundo juega un papel fundamental. El tratamiento quirúrgico clásico de esta afección ha sido la neurectomía por medio de un abordaje abierto con las complicaciones potenciales asociadas a dicho procedimiento. El presente artículo explica el abordaje personal del autor de esta patología mediante una descompresión del nervio, seccionando el ligamento tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Though this attempt to create more space for the MN by cutting the DTML is a very common technique, no publication has been found that measures this space and that connects it with MN. For this reason, our results may be reinforced amidst the great variety of surgical techniques which aim at freeing the DTML to create more space for the MN [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 92%
“…Though this attempt to create more space for the MN by cutting the DTML is a very common technique, no publication has been found that measures this space and that connects it with MN. For this reason, our results may be reinforced amidst the great variety of surgical techniques which aim at freeing the DTML to create more space for the MN [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 92%